Tools for pest and disease management by stakeholders: a case study on Plantwise - Otieno, Washington (Burleigh Dodds Series in Agricultural Science, 2021)
This chapter presents Plantwise as an innovative process for pest management in small holder crop production systems. The tools and applications developed under Plantwise constitute innovations that have potential to contribute to broad aspects of pest management. They can be easily repurposed to address specific needs and adapted to fit various country contexts and agricultural production practices.